PTH-039 Should Anticoagulants be Stopped Before Diagnostic Colonoscopy?. (4th June 2013) - Vaughan-Shaw, P G; Rai, P; Goodman, A; Aung, M
Abstract : Introduction: With increasing age and polypharmacy, an increasing proportion of patients undergoing diagnostic colonoscopy take anticoagulant medication. Under UK guidelines anticoagulants are continued for diagnostic colonoscopy and which may necessitate a second colonoscopy for 'high risk' procedures after stopping anti-coagulants. This may increase endoscopy waiting times and subject often frail patients to a second invasive procedure. This study aims to identify the incidence of and indication for repeat colonoscopy. Methods: All colonoscopies performed over a 3 year period were studied. Any patients that underwent 2 colonoscopies within a 12-month period were included. Data on colonoscopy indication and outcome were collected. Results: 5747 colonoscopies were performed over the study period. Of these, 193 colonoscopies were repeats performed within 12 months. Incomplete colonoscopy (n = 54) due to poor bowel preparation (n = 45) was the commonest indication for a repeated procedure. Requirement for endoscopic mucosal resection (EMR) or polypectomy indicated a repeat colonoscopy in 48 cases. Patients requiring EMR on warfarin (n = 12) or clopidigrel (n = 2), accounted for 7% of all repeated colonoscopies with a median delay repeat colonoscopy of 37 days. There was no morbidity associated with repeated colonoscopy in this series. Conclusion: Repeated colonoscopy due to previous anti-coagulation accounts for a small proportion (7%) of repeated procedures and an insignificant proportion (0.2%) of all colonoscopies performed. Cessation of anti-colagulation for diagnostic colonoscopy would not result in a significant reduction in endoscopy workload but subject patients to an unnecessary risk of thromboembolic disease. Disclosure of Interest: None Declared.